Tourism and European capitals of culture: the role of destination competitiveness governance. (17th February 2009) - Paskaleva, Krassimira; Besson, Edith; Sutherland, Margaret
Cultural tourism – let alone its urban dimensions – is said to require integrated, whole system thinking to bring about the sustainable and competitive destination. This paper explores how these contending forces are being played out in tourist cities participating in the European Capital of Culture Programme (ECOC). Specifically, the potential of ECOC as a cultural tourism response strategy is examined through literature review and case studies. Destination competitiveness governance is proposed as a framework for evaluation. Innovation of policy in the discourses of the city and cultural tourism is discussed as a co-creation of activity and process that stems from the stakeholder interaction.